Development of Learning Tools Based on Geogebra-Assisted Inquiry Learning Models to Improve Students' Mathematical Reasoning Abilities - Silalahi, Joshua Pandapotan; Siagian, Pargaulan Pargaulan; Mukhtar, Mukhtar Mukhtar (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
The Geogebra-assisted inquiry learning paradigm was created to increase students' mathematical thinking. This research will identify the learning device. This is development research. This study will be done in SMA Negeri 1 Gebang, Jl. Diponogoro, Pekan Gebang, Kecamatan Gebang, Kab. Langkat, North Sumatra 20856. The research found: 1) The device is valid. 2) The device developed is practical with an average value of 3.07 (category "Medium") and 4.04 (category "High"); 3) it is effective because (a) the final test of students' Mathematical Reasoning abilities was 52% with 21 students (58.33%) declared complete and trial II 30 students (83.34%). (b) Trial I's student response questionnaire score was 89% and trial II's 95%. 4) Students' mathematical thinking improved with a 0.28 score (0.3 < gâ‰¤0.7) in trial 1 and a 0.67 score (0.3 < N-Gain â‰¤0.7) in trial II, meeting the "moderate" criterion.